Karakteristik Kekerasan Perunggu Sebagai Material Gambelan Pada Proses Casting Pembuatan Gambelan Bali - Putra, Dewa Nyoman Tri Astawa; Sugita, I.K.G; Negara, DNK Putra (Teknik Desain Mekanika; Vol 13 No 3 (2024): Juli 2024 : Teknik Desain Mekanika, 2024)
Abstract Bronze is an alloy material of copper (Cu) with tin (Sn), generally bronze is the material used in making gambelan. Making gambelan goes through several process stages, namely casting, forging and heat treatment. The gambelan manufacturing process greatly influences the mechanical properties produced. Casting is a manufacturing process in which metal materials are melted and molded to produce a product that approximates the geometric shape of the product. This research uses testing of mechanical properties, especially hardness in the casting process. Stages in the process casting manufacturing, has almost the same value in all three tones, the highest hardness value is obtained in the dang tone with a value of 138.33 VHN and in the dong tone it obtains a hardness value of 137.23 VHN, in the ding tone it obtains a hardness value of 138.40 VHN. Keywords: bronze, casting,hardness